Effect of the mutual position between weld seam and reinforcement on the residual stress distribution in Friction Stir Welding of AA6082 skin and stringer structures. (June 2016) - Buffa, G.; Fratini, L.; Marannano, G.; Pasta, A.
Abstract: In the paper, a numerical and experimental study was carried out to highlight the effect of the distance d between the weld seam and the reinforcement on the residual stress distribution in Friction Stir Welded AA6082-T6 structures. An L-shaped profile was welded to a sheet metal with varying tool rotation and distance d from the weld seam. The Cut Compliance method was used to determine the resulting longitudinal residual stress. A dedicated FE model for FSW was set up, validated and utilized to predict the longitudinal residual stress in the assembled part. The analysis allowed the identification of a few design guidelines in order to reduce the detrimental effects of the residual stresses. Highlights: Compressive residual stress state is found away from the weld seam. Larger tensile stress is found in correspondence of the weld seam. Residual stress only slightly increases with tool rotation and distance d . d =50 mm allows to counterbalance crack nucleation and growth in the stringer area.